A not B task and language in infants with early brain lesions - Brozović, Blaženka (Array, 2003)
Since Piaget first introduced the term object permanence, today elaborated in A not B task, the problem itself has undergone many different theoretical explanations and methodological adaptations. Our research on communicative and language development in children with early brain lesions focuses on a number of different variables including performance on the A not B task as one of the working memory indicators. Success on the A not B task shows progression with age. Results of neuropsychiological research on rhesus monkeys have shown that the maturation of dorsolateral prefrontal cortex underlies this improvement. Considering the important role of the prefrontal cortex in the development of the working memory capacity -spatial and phonological, and the fact that the latter is essential for language development, we compared task performance and language on two groups of infants: five healthy infants and five infants with early brain lesions (pre-perinatal ischemic and/or hemorrhagic lesions: grade I-III). The measure of performance on A not B was the length of delay necessary to provoke error reflected in perseverative reaching. Once a month the variables relevant for A not B task were assessed and we also followed other aspects of development: mental, behavioral and motor mildstones (The Bayley Scales of Infant Development), expressive and receptive vocabulary (Croatian version of MacArthur Communicative Developmental Inventories). In data analysis we focused on getting insight on relations between the onset of the expressive and receptive vocabulary and success on the A not B task. Preliminary results indicate that subjects with early brain lesions make the A not B error at shorter delays than healthy subjects. A clear connection between the success at the A not B task and development of the vocabulary was not found which could speak in favor of separate developmental trajectories of the two working memory components.